2011
DOI: 10.1159/000332592
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect between BRAP Polymorphism and Diabetes on the Extent of Coronary Atherosclerosis in the Chinese Population

Abstract: Objectives: Coronary artery disease (CAD) is a multifactorial disease and influenced by genetics. We previously reported that a single nucleotide polymorphism (rs11066001) in the BRAP gene was related to the risk of myocardial infarction. However, it is unclear whether rs11066001 is associated with the extent of coronary atherosclerosis. Methods: We enrolled 732 patients scheduled for diagnostic coronary angiography. Angiographic presence of significant CAD (0 or 1), clinical vessel score (CVS, 0–3 vessels) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
1

Year Published

2012
2012
2013
2013

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
0
4
0
1
Order By: Relevance
“…SNP rs11066001 in the BRAP gene has been shown to be significantly associated with MI/CAD [8,9,11], carotid plaques [14] and Ankle-Brachial index (ABI) [12,13]. These associations imply that its genetic effect might be more evident in large artery atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SNP rs11066001 in the BRAP gene has been shown to be significantly associated with MI/CAD [8,9,11], carotid plaques [14] and Ankle-Brachial index (ABI) [12,13]. These associations imply that its genetic effect might be more evident in large artery atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…BRAP polymorphisms have been related to metabolic syndrome in a Chinese population [37], MI/CAD in Japanese, Korean and Taiwanese populations [9-11], and ABI and carotid atherosclerosis in a Taiwanese population [12-14]. Only one report showed that a BRAP polymorphism was associated with metabolic syndrome in European American and African American populations [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 The single nucleotide polymorphisms (SNPs) in BRAP were significantly associated with coronary artery disease in Asian populations. 12,14 Hsu et al 15 reported that the SNP (rs11066001) in BRAP has a synergistic effect with diabetes in the Chinese population.…”
Section: Introductionmentioning
confidence: 99%
“…Einteilung des Koronargefäßsystems in 15 Abschnitte und eine unterschiedliche Gewichtung der Läsion je nach Lokalisation)(Hsu et al 2011). Auch das Risiko für das Auftreten von atherosklerotischen Läsionen in der A. carotis ist bei Vorliegen des GG-Genotyps (SNP rs11066001, 270A>G) 1,58-fach erhöht.Liao et al fanden in dem Zusammenhang, dass BRAP durch Lipopolysaccharid, nicht aber durch artifiziell oxidiertes LDL in aortalen, glatten Muskelzellen induziert wird.…”
unclassified